2018
DOI: 10.1002/fam.2674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trace chloride on the char formation and flame retardancy of the LLDPE filled with NiAl‐layered double hydroxides

Abstract: Summary Layered double hydroxides (LDHs) have received intensive attentions for the potential as flame retardants of polyolefin. In the work, trace amounts of chloride were investigated for their synergistic effects on the char formation and flame retardancy of the linear low‐density polyethylene (LLDPE) filled with NiAl‐LDHs. Results showed that 0.5 wt% of NH4Cl incorporation enabled the char yield of 20%LDH/LLDPE (20 wt% of NiAl‐LDH) increase from 10.4% to 49.6%. Other chlorides likewise offered significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…e presence of such low amounts of lignin by itself did not increase the ame retardancy of FPF, but the addition of E560 increased the charring e ciency, while the addition of LDH contributed to reinforcing the char layer, yielding a more cohesive protective layer that decreased the pHRR to 47% as compared with an un lled foam 0E. Wang et al [176] investigated the synergistic e ects of trace amounts of chloride on char formation and ame retardancy of linear low density polyethylene (LLDPE) lled with NiAl-LDHs.…”
Section: Layered Doublementioning
confidence: 98%
See 1 more Smart Citation
“…e presence of such low amounts of lignin by itself did not increase the ame retardancy of FPF, but the addition of E560 increased the charring e ciency, while the addition of LDH contributed to reinforcing the char layer, yielding a more cohesive protective layer that decreased the pHRR to 47% as compared with an un lled foam 0E. Wang et al [176] investigated the synergistic e ects of trace amounts of chloride on char formation and ame retardancy of linear low density polyethylene (LLDPE) lled with NiAl-LDHs.…”
Section: Layered Doublementioning
confidence: 98%
“…LDHs can be directly used as ame retardant additives because of their unique chemical properties and layered structures [170][171][172][173][174][175][176][177]. For example, exible polyurethane foam with samples containing 10% ame retardant, the LOI increased from 20.8 to 29.0, the UL-94 rating increased from no to V-0, and the pHRR decreased from 1090 to 284 kW/m 2 , respectively.…”
Section: Silicon-containing Compoundsmentioning
confidence: 99%
“…However, due to the poor compatibility of flame retardants such as aluminum hydroxide and ammonium polyphosphate (APP) with PE, the mechanical properties of PE will decline while improving the flame retardancy of PE, curtailing the application of flame retardant PE. [11][12][13] Therefore, researchers usually use modified additives, synergistic flame retardants or new flame retardant by synthesis to deal with the poor compatibility of flame retardant and PE. When using magnesium hydroxide (MH) to Flame Retardant PE, Yang et al [14] found that MH would destroy the structure of PE composite and seriously reduce the mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…This is not only due to LDHs can produce water and carbon dioxide to dilute flammable gases at a fire, but also the metal ions in the LDHs have a catalytic effect on the char formation during the polymer degradation process 10 . Especially, previous studies revealed the presence of non‐noble transition metal ions, such as Ni 2+ exhibits higher catalytic activity than the common metal ions Mg 2+ due to valence electron structure, endowing better flame retardancy 11,12 . For instance, Jaerper S. and his colleague compared three kinds of different metal constituents (Zn, Co and Ni) alkyl‐substituted LDHs for flame‐retardant low‐density polyethylene (LDPE).…”
Section: Introductionmentioning
confidence: 99%
“…10 Especially, previous studies revealed the presence of non-noble transition metal ions, such as Ni 2+ exhibits higher catalytic activity than the common metal ions Mg 2+ due to valence electron structure, endowing better flame retardancy. 11,12 For instance, Jaerper S. and his colleague compared three kinds of different metal constituents (Zn, Co and Ni) alkyl-substituted LDHs for flame-retardant low-density polyethylene (LDPE). The results found that the flammability reduction for NiAl-LDHs nanocomposites (2.0% fillers with 18% of reduction) was better than that of ZnAl-LDHs (2.0% fillers with 10% of reduction) nanocomposites.…”
Section: Introductionmentioning
confidence: 99%